Penerapan Metode Economic Order Quantity (EOQ) Dalam Pengendalian Persediaan Bahan Baku Pada Industri Rumahan Tahu Susu XYZ - Farhan Firmansyah; Sutrisno Sutrisno (Jurnal Ilmiah Wahana Pendidikan, 2022)
XYZ Milk Tofu Home Industry is a Home Industry that is quite developed and is able to meet market demand in several regions, it's just that in this case the form of the need for the preparation of raw materials is still fairly manual or traditional using only instinct or estimates, so you have to order raw materials over and over again which results in an increase in ordering costs. The purpose of this study is to increase the maximum ordering capacity. The method used is EOQ (Economic Order Quantity) by taking into account ordering costs and storage costs. The application of the EOQ method is expected to be able to handle the problems that have occurred so far. Based on the results of cost analysis, orders increased from 90.20 Kilograms to 408,29 Kilograms. With the EOQ (Economic Order Quantity) method, it can also be seen that the value of the Safety Stock is 267 Kilograms and the Pre-Order Point is 19 Kilograms, to prevent delays in the supply of raw materials. The conclusion of this research is that by applying the EOQ method, it is proven that production costs in the production of milk tofu can be reduced to get a more optimal profit.